PENGARUH OPERATIONAL EFFICIENCY LAYANAN BANQUET TERHADAP GUEST SATISFACTION HOTEL DOUBLETREE BY HILTON JAKARTA DIPONEGORO - Viona Oktaviana; Nila Rifai (Lembaga Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Pariwisata Bogor, 2025)
The hospitality industry is part of the rapidly evolving service sector and contributes significantly to the global economy, particularly through the provision of accommodation services and additional facilities that enhance guest comfort. Star-rated hotels such as DoubleTree by Hilton Jakarta offer high-quality services including banquet services for events such as weddings, conferences, and business meetings. The study aims to obtain information on the effect of operational efficiency of banquet services on guest satisfaction at DoubleTree by Hilton Jakarta Diponegoro Hotel. This study adopts a quantitative method with a descriptive approach, and data collection techniques through questionnaires. to 84 respondents who have attended banquet events at the hotel. The research tool was tested using validity and reliability testing. The results of the validity test showed that all question items were valid, while the reliability test produced a Cronbach's Alpha value of 0.935 for the operational efficiency variable and 0.953 for the guest satisfaction variable, which means that all items are reliable. The results of the linear regression analysis directly illustrate that operational efficiency has a significant effect on guest satisfaction with a significance value of 0.000 and a regression coefficient of 0.902. From these results, it can be concluded that the more efficient the banquet service provided by the hotel, the higher the satisfaction experienced by the guests. This finding is the basis for hotel management to continue to improve coordination between staff, speed of service, and professionalism in banquet service operations in order to maintain competitiveness in the hotel industry.